Phonological Processes in Malayalam Speaking 3-4 Year Old Urban and Rural Children - Anitha Simon, Shruthi L. Rajalekshmi S., Jenny Mevis D’Souza and Satish Kumaraswamy (Language in India, 2015)
Most of the Indian population resides not in urban, but in rural areas with living conditions and facilities being very much different from the urban conditions. Hence, the present study focusses on comparing the phonological processes across urban and rural in the Malayalam speaking children of India. Thirty typically developing children, age ranging from 3-4 years participated in the study. The speech sample (minimum 50 utterances) was recorded from each child in a quiet room at home or school environment and recorded using PRAAT software. The result of the present study was that rural children exhibit more phonological processes than urban group.